Synchronised phosphorylation of BNIP3, Bcl-2 and Bcl-xL in response to microtubule-active drugs is JNK-independent and requires a mitotic kinase. - Mellor, H; Rouschop, K; Wigfield, S; Wouters, BG; Harris, A (2010)
BNIP3 is a hypoxia-inducible BH3-only member of the Bcl-2 family of proteins that regulate apoptosis and autophagy. However the role of BNIP3 in the hypoxia response has proved difficult to define and remains controversial. In this study we show that in cancer cells, knockdown or forced expression of BNIP3 fails to modulate cell survival under hypoxic or normoxic conditions. However, we demonstrate that BNIP3 is regulated post-translationally, existing as multiple monomeric and dimeric phosphorylated forms. Upon treatment with microtubule inhibitors, but not other classes of chemotherapeutics, BNIP3 becomes hyperphosphorylated. We demonstrate that the phosphorylation of BNIP3 occurs in synchrony with phosphorylation of its binding partners Bcl-2 and Bcl-xL. Microtubule inhibitor-induced phosphorylation of these proteins occurs independently of the AKT/mTor and JNK kinase pathways and requires Mps1 mitotic checkpoint kinase activity. Inhibition of mitotic arrest in the presence of paclitaxel blocks the phosphorylation of BNIP3, Bcl-2 and Bcl-xL, demonstrating that these proteins are phosphorylated by a mitochondrially active mitotic kinase. We show that phosphorylation increases the stability of BNIP3 and that BNIP3 predominantly interacts with the phosphorylated form of Bcl-2. This study provides new insight into the post-translational functional control of these Bcl-2 family members.